Historical Experience with Bond Financing to Developing Countries - Laursen, Thomas (IMF Working Papers; Working Paper ;, 1995)
The paper reviews the historical experience of developing countries with bond issues in international markets in order to put the recent wave of bond financing by these countries in some perspective. It examines developments in the early part of this century and during the mid-1970s and early 1980s. The sources and the role played by bond financing during these periods are discussed. The payments problems associated with these bonds that emerged during the 1930s and during the latter half of the 1980s and the ways in which these problems were resolved are also examined.